Synthesis and Characterization of Nanocomposite Hydroxy-Sodalite/Ceramic Membrane via Pore-Plugging Hydrothermal Synthesis Technique - Daramola, M.O.; Dinat, A.; Hasrod, S. (Journal of Membrane and Separation Technology, 2015)
In this article, synthesis and characterization of nanocomposite hydroxy sodalite (H-SOD)/α-alumina membrane via the so-called “pore-plugging” hydrothermal synthesis (PPH) protocol is reported for the first time. In nanocomposite architecture membranes, zeolite crystals are embedded within the pores of the supports instead of forming thin-film layers of the zeolite crystals on the surface of the supports. The as-prepared membranes were characterized with SEM and FTIR for morphology and purity of the H-SOD crystals. Compared to the conventional in-situ direct hydrothermal synthesis, membranes obtained from PPH possess higher mechanical and thermal stability. In addition, defect control with nanocomposite architecture membrane is possible because the zeolite crystals are embedded within the support pores of the membrane, thereby limiting the maximum defect size to the pore sizes of support. The nanocomposite architecture nature of the membranes safeguards the membrane from shocks or abrasion that could promote defects/inter-crystalline pores formation. These advantages could be helpful in the scale-up process of the preparation procedure of membranes at the commercial level with less-demanding conditions.